2021
DOI: 10.5194/acp-21-13167-2021
|View full text |Cite
|
Sign up to set email alerts
|

Methane (CH<sub>4</sub>) sources in Krakow, Poland: insights from isotope analysis

Abstract: Abstract. Methane (CH4) emissions from human activities are a threat to the resilience of our current climate system. The stable isotopic composition of methane (δ13C and δ2H) allows us to distinguish between the different CH4 origins. A significant part of the European CH4 emissions, 3.6 % in 2018, comes from coal extraction in Poland, the Upper Silesian Coal Basin (USCB) being the main hotspot. Measurements of CH4 mole fraction (χ(CH4)), δ13C, and δ2H in CH4 in ambient air were performed continuously during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 47 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…than Za Miastem on 7 June. Thus, the background concentration field has some spatial variability which might be connected to remote sources such as the Krakow urban region affecting The Glade but not Za Miastem (Menoud et al, 2021). In the future, we will aim at estimating errors due to spatial background variability by running a model that includes all known sources in a larger area around the target region or by deploying more spectrometers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…than Za Miastem on 7 June. Thus, the background concentration field has some spatial variability which might be connected to remote sources such as the Krakow urban region affecting The Glade but not Za Miastem (Menoud et al, 2021). In the future, we will aim at estimating errors due to spatial background variability by running a model that includes all known sources in a larger area around the target region or by deploying more spectrometers.…”
Section: Discussionmentioning
confidence: 99%
“…Using airborne imager data, Krautwurst et al (2021) found some discrepancies between their estimates and the E-PRTR inventory for small groups of ventilation facilities. The isotopic CH 4 composition was measured by Menoud et al (2021) with ground-based in situ instruments. Swolkień (2020) discusses the short-term, shaft-wise CH 4 release in the USCB.…”
Section: Introductionmentioning
confidence: 99%
“…The isotopic composition was determined by analyzing the samples stored in the Tedlar bags using a continuous flow isotope ratio mass spectrometer system. More details about the analytical system and the calibration are provided in Brass and Röckmann, 2011;Röckmann et al, 2016;Menoud et al, 2021. Out of the 59 flights performed during this study, the air samples from 34 flights were stored in Tedlar bags for further analysis of isotopic composition.…”
Section: Uav-based Active Aircore Systemmentioning
confidence: 99%
“…It is still difficult to assess the scale of CO 2 and CH 4 emissions from landfill facilities due to the large temporal and spatial variations in the landfill source strength [7,19,20]. The combination of high-resolution atmospheric and precise stable isotope measurements acts as an effective tool for monitoring the strength of major CO 2 and CH 4 sources and understanding GHGs biogeochemistry [21][22][23][24][25]. The ranges of isotopic signatures (δ 13 C) of carbon dioxide and methane emitted from the major source categories are very large.…”
Section: Hydrolysis (In Thementioning
confidence: 99%
“…The ranges of isotopic signatures (δ 13 C) of carbon dioxide and methane emitted from the major source categories are very large. With respect to carbon isotopic fractionation during methanogenesis, three types of methane sources have distinct δ 13 C signatures, whereby biogenic CH 4 is heavily depleted in 13 C (from −75 to −55‰) [26,27] whereas thermogenic methane typically has δ 13 C values (from −60 to −20‰) [28,29] and pyrogenic methane is assigned more enriched values (−50 to −40‰) [21,30]. The isotopic range of δ 13 C(CO 2 ) for terrestrial vegetation varies from −29 to −12‰ [31,32] whereas the δ 13 C composition of fossil fuel combustion ranges from −44‰ to −22‰ [22,33].…”
Section: Hydrolysis (In Thementioning
confidence: 99%